A STUDY ON THE CUSTOMER ATTITUDE TOWARDS INTERNET BANKING SERVICES WITH REFERENCE TO MAYILADUTHURAI. - BALASUBRAMANIAN, P.; KALIDOSS, K. (International Journal of Psychosocial Rehabilitation, 2025)
Internet banking services first come into view in the early 1990’s, when telephone banking, credit card and ATM services are three important applications. In the last decade, information system, databaseand other technologies are applied into services in the banking at various levels. The availability of e-banking services, internet facility is now conducted through a secure website operated by local banks and includes online enquiry, e- payments, e-transfer and the like.This article paper highlights that customer attitude towards internet banking services.